The Effect of Pulmonary Rehabilitation on The Duration of Antibiotic Switches, IL-10 Levels and PEFR Values in Hospitalized Community Pneumonia Patients - Mariyatul Khiptiyah; Iin Noor Chozin; Suryanti Dwi Pratiwi; Rahmad Rahmad; Harun Al Rasyid (Jurnal Respirologi Indonesia, 2020)
Background: Pneumonia is an acute inflammation of the lung parenchyma and ranked third of 30 causes of death in the world. WHO estimates the death caused by pneumonia is 1.6 million per year. Long duration of antibiotic switches is associated with increased morbidity, nosocomial infections and costs of healthcare. This study aims to assess the effect of pulmonary rehabilitation with the duration of antibiotic switches and interleukin-10 (IL-10) levels of pneumonia patients in non-intensive care thus pulmonary rehabilitation can be routinely use as adjuvant therapy. Methods: The study was conducted in May-November 2019 at Saiful Anwar Hospital Malang, with 40 pneumonia patients in the non-intensive care and divided in two groups which contains of 20 patients. This study uses consecutive simple random sampling. In treatment group, pulmonary rehabilitation consists of breathing exercise, effective cough techniques, clapping, postural drainage and breathing muscle exercises with spirometry incentive tools. The pulmonary rehabilitation treatment was done by Medical Rehabilitation Department of Saiful Anwar Malang Hospital. IL-10 levels and PEFR values on the zero and fifth days of treatment were measured. Results: The duration of antibiotic switches received pulmonary rehabilitation was shorter 5.05 days (P